The Surface Wave Scattering-Microwave Scanner (SWS-MS). (January 2016) - Geffrin, Jean-Michel; Chamtouri, Maha; Merchiers, Olivier; Tortel, Hervé; Litman, Amélie; Bailly, Jean-Sébastien; Lacroix, Bernard; Francoeur, Mathieu; Vaillon, Rodolphe
Abstract: The Surface Wave Scattering-Microwave Scanner (SWS-MS) is a device that allows the measurement of the electromagnetic fields scattered by objects totally or partially submerged in surface waves. No probe is used to illuminate the sample, nor to guide or scatter the local evanescent waves. Surface waves are generated by total internal reflection and the amplitude and phase of the fields scattered by the samples are measured directly, both in the far-field and the near-field regions. The device's principles and their practical implementation are described in details. The surface wave generator is assessed by measuring the spatial distribution of the electric field above the surface. Drift correction and the calibration method for far-field measurements are explained. Comparison of both far-field and near-field measurements against simulation data shows that the device provides accurate results. This work suggests that the SWS-MS can be used for producing experimental reference data, for supporting a better understanding of surface wave scattering, for assisting in the design of near-field optical or infrared systems thanks to the scale invariance rule in electrodynamics, and for performing nondestructive control of defects in materials.